Structure-property relations of ferroelectric BaTiO 3 ceramics containing nano-sized Si 3N 4 particulates - Namsar O. (2014)
Barium titanate/silicon nitride (BaTiO 3/xSi 3N 4) powder (when x = 0, 0.1, 0.5, 1 and 3 wt%) were prepared by solid-state mixed-oxide method and sintered at 1400°C for 2 h. X-ray diffraction result suggested that tetragonality (c/a) of the BaTiO 3/xSi 3N 4 ceramics increased with increasing content of Si 3N 4. Density and grain size of BaTiO 3/xSi 3N 4 ceramic were found to increase for small addition (i.e. 0.1 and 0.5 wt%) of Si 3N 4 mainly due to the presence of liquid phase during sintering. BaTiO 3 ceramics containing such amount of Si 3N 4 also showed improved dielectric and ferroelectric properties. © 2011 Elsevier Ltd and Techna Group S.r.l.